2017
DOI: 10.21037/tgh.2017.04.10
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional computed tomography simulation for laparoscopic lymph node dissection in the treatment of proximal gastric cancer

Abstract: Application of laparoscopic surgery (LS) has expanded worldwide in the various fields due to the potential advantage of being less invasive than open surgery; however difficulty in recognizing positional relationship of the organs is one of the disadvantages of this kind of surgery. In order to compensate this drawback, preoperative three-dimensional computed tomography (3D-CT) simulation is regarded as promising. In gastric cancer surgery, 3D-CT simulation seems particularly effective in the splenic hilar dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This is because conventional two-dimensional (2D)-CT images cannot be rotated and we could not simulate the organ positional relationship in the actual view, including that of the dorsal landmark of No. 11p LN dissection using 2D-CT. 8,9 Recently, three-dimensional (3D)-CT has been used for preoperative simulation in numerous surgeries. Several studies on gastric surgery have demonstrated the usefulness of prediction for splenic hilum or perigastric vessels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because conventional two-dimensional (2D)-CT images cannot be rotated and we could not simulate the organ positional relationship in the actual view, including that of the dorsal landmark of No. 11p LN dissection using 2D-CT. 8,9 Recently, three-dimensional (3D)-CT has been used for preoperative simulation in numerous surgeries. Several studies on gastric surgery have demonstrated the usefulness of prediction for splenic hilum or perigastric vessels.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on gastric surgery have demonstrated the usefulness of prediction for splenic hilum or perigastric vessels. [8][9][10] However, there is no study on the prediction of anatomical landmarks during LN dissection in gastric surgery using preoperative 3D-CT. Moreover, it is still unclear whether 3D-CT improves surgical outcomes in laparoscopic gastrectomy with No.…”
Section: Introductionmentioning
confidence: 99%